(3GdeTQb ajeG jMGVQ Hg ef BOGH GdeTQbs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s ((3GdTjN MSf GdYWGQ TjN GdCRgQ s)
(3ChdgG (B:s
(3ai GdNHQ Cf GdegOi deG ONd GdeOjfI s
(3BNQgG (B:s
(3ced GdSaQ GdKGfi ef cJGH GdeTQb s
(3GdLRA GdKGfi eUhQ Yf CUd HNW GdeDda ceG PcQ ai CNQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B337 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B248 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , HgG NQe s
Keywords: (3GdJGQjNs